Emerging role of extracellular vesicles in kidney diseases - Xiang, Huiling; Zhang, Chun; Xiong, Jing (Frontiers in Pharmacology, 2022)
Many types of renal disease eventually progress to end-stage renal disease, which can only be maintained by renal replacement therapy. Therefore, kidney diseases now contribute significantly to the health care burden in many countries. Many new advances and strategies have been found in the research involving kidney diseases; however, there is still no efficient treatment. Extracellular vesicles (EVs) are cell-derived membrane structures, which contains proteins, lipids, and nucleic acids. After internalization by downstream cells, these components can still maintain functional activity and regulate the phenotype of downstream cells. EVs drive the information exchange between cells and tissues. Majority of the cells can produce EVs; however, its production, contents, and transportation may be affected by various factors. EVs have been proved to play an important role in the occurrence, development, and treatment of renal diseases. However, the mechanism and potential applications of EVs in kidney diseases remain unclear. This review summarizes the latest research of EVs in renal diseases, and provides new therapeutic targets and strategies for renal diseases.